1997
DOI: 10.1007/bf02764847
|View full text |Cite
|
Sign up to set email alerts
|

Apical vault repair, the cornerstone or pelvic vault reconstruction

Abstract: Pelvic organ prolapse remains a difficult problem for pelvic reconstructive surgery. Before new surgical procedures can be developed a good understanding of pelvic anatomy is necessary. It is widely held that the etiology of pelvic organ prolapse is secondary to stretch neuropathy following childbirth and chronic cough or constipation. Several transvaginal and transabdominal procedures have been developed over the years. With the increasing use of laparoscopy, a new variation on existing culdeplasty techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…Ross later described the pericervical fascia as the cornerstone of pelvic reconstruction [9]; this structure, however, is not always addressed during vaginal hysterectomy with anterior and posterior colporrhaphy. Since that time, various authors have reported their experiences with reconstructive pelvic surgery with uterine preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Ross later described the pericervical fascia as the cornerstone of pelvic reconstruction [9]; this structure, however, is not always addressed during vaginal hysterectomy with anterior and posterior colporrhaphy. Since that time, various authors have reported their experiences with reconstructive pelvic surgery with uterine preservation.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6 The reconstruction of the vaginal tube requires that the upper edges of the pubocervical and rectovaginal fascia should be closed; reestablishing suspension requires that the repaired vagina be suspended to a normal segment of the cardinal/uterosacral ligament complex 3,5,6 ( Figure 4) or some other procedure like sacrocolpopexy or sacrospinous fixation. 5 Good apical vault support is the corner stone of pelvic reconstruction 7 when this is achieved, repair of level II support failure to reattach the rectovaginal fascia laterally to the iliococcygeal fascia and/or attach the pubocervical fascia anteriorly to arcus tendinous fascia pelvis (paravaginal repair) should be considered. 3,5,6 Concurrent anterior and/or posterior repair of midline fascial defect is also undertaken when appropriate.…”
Section: Treatmentmentioning
confidence: 99%
“…17,18,19,20 The abdominal approach includes sacrocolpopexy 1,21,22 and abdominal uterosacral suspension. 21 Laparoscopic sacrocolpopexy 7 and laparoscopic uterosacral suspension have also been described. 3,6 Transvaginal uterosacral suspension…”
Section: Surgical Optionsmentioning
confidence: 99%
See 2 more Smart Citations